THE IMPORTANCE OF SONGS IN TEACHING ENGLISH - Temirova , Sayyora Mirmakhmud qizi; Kamola Malikovna , Akabirova (Educational Research in Universal Sciences, 2023)
This article explores the importance of integrating songs into English language teaching, highlighting their potential to enhance students’ language skills and create an engaging learning environment. The use of songs in the EFL classroom is discussed, with emphasis on their impact on vocabulary, grammar, pronunciation, and listening skills. Techniques for effectively incorporating songs into lessons, such as gap filling activities, are also outlined. The article emphasizes the need for teachers to be familiar with various methods and technologies for using songs in teaching, and to adapt these approaches as necessary to maximize their effectiveness.